The regulation of inhibitor of apoptosis proteins (IAPs) during the apoptosis of Cotesia chilonis - Lu, Ming-Xing; He, Fu-Jing; Zhu, Feng; Du, Yu-Zhou (Frontiers in Physiology, 2023)
Inhibitor of apoptosis proteins (IAPs) are crucial components of apoptosis that perform vital roles in the regulation of caspase activity in organisms. In this study, two IAPs genes were identified from Cotesia chilonis, the dominant parasitic wasp of Chilo suppressalis. CcIAP1 gene is a typical IAP and contains two BIR domains and a RING domain, whereas CcIAP gene is an atypical IAP1 only containing two BIR domains. Phylogenetic analysis indicated that CcIAP1 and CcIAP were grouped with other Hymenopteran IAPs and IAP1 in C. suppressalis. Real-time quantitative PCR revealed that CcIAP1 and CcIAP genes were both highly induced at −6°C and 30°C, and expression was highest at the third instar stage. The expression of CcIAP1 and CcIAP genes were significantly induced during parasitism of C. suppressalis, and the 7-d time point resulted in the highest expression levels for both genes, in which was an advanced stage of larval development of C. chilonis. RNAi experiments showed that CcIAP1 gene was the key IAP in the regulation of apoptosis of C. chilonis and its host. In conclusion, CcIAP1 and CcIAP correlate with the development of C. chilonis and their responses to temperature stress.